2016
DOI: 10.1017/s2045796016000044
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and psychosocial wellbeing of Syrians affected by armed conflict

Abstract: Aims. This paper is based on a report commissioned by the United Nations High Commissioner for Refugees, which aims to provide information on cultural aspects of mental health and psychosocial wellbeing relevant to care and support for Syrians affected by the crisis. This paper aims to inform mental health and psychosocial support (MHPSS) staff of the mental health and psychosocial wellbeing issues facing Syrians who are internally displaced and Syrian refugees.Methods. We conducted a systematic literature sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
451
2
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(490 citation statements)
references
References 47 publications
21
451
2
16
Order By: Relevance
“…Although these symptoms are found to be prevalent, some studies remarked high levels of resilience among this particular refugee group and suggested that such manifestations do not necessarily indicate psychopathology (e.g. posttraumatic stress disorder, depression), unless they cause intense distress and functional impairment [15]. Congruently, a growing number of research emphasize the importance of the establishment of the interventions that promote such resiliency in coping with distress among Syrian refugees [16].…”
Section: Major Challenges: Mental Health Risks and Service Utilizatiomentioning
confidence: 99%
“…Although these symptoms are found to be prevalent, some studies remarked high levels of resilience among this particular refugee group and suggested that such manifestations do not necessarily indicate psychopathology (e.g. posttraumatic stress disorder, depression), unless they cause intense distress and functional impairment [15]. Congruently, a growing number of research emphasize the importance of the establishment of the interventions that promote such resiliency in coping with distress among Syrian refugees [16].…”
Section: Major Challenges: Mental Health Risks and Service Utilizatiomentioning
confidence: 99%
“…Refugees are at considerable risk of developing symptoms of common mental disorders including depression, anxiety, posttraumatic stress disorder (PTSD) and related somatic health symptoms (de Jong, Komproe, & Van Ommeren, 2003; Fazel, Wheeler, & Danesh, 2005; Hassan, Ventevogel, Jefee-Bahloul, Barkil-Oteo, & Kirmayer, 2016; Steel et al, 2009). Epidemiological studies indicate that the age-standardized point prevalence of PTSD and major depression in conflict-affected populations is estimated to be 12.9% and 7.6%, respectively (Charlson et al, 2016).…”
Section: Common Mental Disorders and Related Conditions In Syrian Refmentioning
confidence: 99%
“…As a comparison, it has been estimated that approximately 4.4% of the world population suffers from major depression (WHO, 2017) and 3.3% from PTSD (Stein et al, 2014). Although good epidemiological data on psychosis is lacking, it is also likely that psychotic symptoms in Syrians have increased (Hassan et al, 2016; Hijazi & Weissbecker, 2015). Child refugees may be especially at risk of developing emotional and behavioural problems, with one study of Syrian refugee children in Turkey reporting that nearly half show clinically significant levels of anxiety and withdrawal (Cartwright, El-Khani, Subryan, & Calam, 2015).…”
Section: Common Mental Disorders and Related Conditions In Syrian Refmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequent influx of refugees in Europe (UNHCR, 2015) is currently dominating the news and the political debate. War experiences, persecution, hunger, loss of loved ones, a long and unsafe journey, and settlement in refugee camps all take their mental and physical toll (de Jong, Komproe, & Van Ommeren, 2003; Hassan, Ventevogel, Jefee-Bahloul, Barkil-Oteo, & Kirmayer, 2016). The resulting long- and short-term mental health and psychosocial consequences are many and varied, and a proportion of refugees seek health care for these mental health problems in their host country (de Jong, 2002; de Jong, Komproe, & Van Ommeren, 2003; Hassan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%